SISTEM PENCATATAN PERGUDANGAN BERBASIS WEBSITE PADA PT PUTRA PERDANA SENTOSA - Dimas Alfarizki (2022)
Along with the rapid development of information technology, one of the influential aspects is the system of recording goods in a warehouse. To support the effectiveness and efficiency of PT Putra Perdana Sentosa in solving the problem of recording goods in the warehouse which is usually done conventionally, it is necessary to prepare a computerized warehousing recording system. The system is expected to facilitate the process of recording goods in an agency, especially PT Putra Perdana Sentosa. In this case, a website-based application is needed which is intended as a system for recording goods or recapitulating goods that are still available. This can shorten the time and make it easier for the company to manage the stock of goods in the warehouse. The purpose of this research is to create a warehousing recording system at PT Putra Perdana Sentosa and produce an interface that can meet user needs. The research method chosen in this research is a qualitative method. Qualitative data is obtained through observations and interviews regarding how the warehousing recording system at PT Putra Perdana Sentosa is currently running. The results of this study indicate that the conventional system of recording goods using handwritten ledgers cannot run effectively, and the absence of a definite recording system makes data collection on goods irregular, resulting in differences in recording existing stock of goods both on the sales and warehousing parties.